Nuclear factor kappa-B signaling is integral to ocular neovascularization in ischemia-independent microenvironment. - Michael DeNiro (Public Library of Science (PLoS), 2014)
Retinal ischemia promotes the upregulation of VEGF expression and accounts for most pathological features of retinal neovascularization (NV). Paradoxically, VEGF remains the pivotal stimulator of ocular NV, despite the absence of ischemia. Therefore, the central question arises as to how the various molecular mechanisms interplay in ischemia-independent NV. It's been suggested that NFκB plays a crucial role in the pathogenesis of diabetic vasculopathies. Here, we dissected the molecular mechanism of ocular NV in the rho/VEGF transgenic mouse model, which develops subretinal NV in ischemia-independent microenvironment. Furthermore, we examined whether intravitreal administration of YC-1, a HIF-1 inhibitor, can modulate the activation of NFκB and its downstream angiogenic signaling in the mouse retina. We demonstrated that YC-1 inhibited retinal NFκB/p65 DNA binding activity and downregulated NFκB/p65, FAK, α5β1, EPO, ET-1, and MMP-9 expression at the message and the protein levels. In addition, YC-1 significantly inhibited subretinal NV by reducing the number of neovascular lesions, the area of each lesion and the total area of NV per retina. We further investigated the influence of VEGF signaling pathway on HIF-1α transcriptional activity to substantiate that this mouse model develops subretinal NV in an ischemia-independent microenvironment. Our data demonstrated that VEGF overexpression didn't have any impact on HIF-1α transcriptional activity, whereas treatment with YC-1 significantly inhibited endogenous HIF-1 activity. Our study suggests that retinal NFκB transcriptional activity is pivotal to ischemia-independent mechanisms, which lead to the local activation of angiogenic cascades. Our data also indicate that the nexus between VEGF and NFκB is implicated in triggering the angiogenic cascade that promotes retinal NV. Hence, targeting the VEGF/NFκB axis may act in a negative feedback loop to suppress ocular NV. This study suggests that inhibition of NFκB activation may be a means of turning off a "master switch" responsible for initiating and perpetuating these ocular pathologies.